Elise the Actress 1865 - Lutz, Norma Jean; Nang ChanYeema (Uhrichsville, Ohio USA Barbour Publishing, Inc., 2005)
Elise likes to perform to help her family and friends forget the dpressing news during the Civil War.
Keywords: Adult Fiction